Chaoshan Guo Molds Culture under Semiotics Theory Creative Product Design - Nong , Linlin; Sirivesmas , Veerawat (Journal of Roi Kaensarn Academi, 2024)
The Chaoshan guo molds is renowned for its extensive range of subjects and diverse symbol systems. Each guo molds serves not only as an exemplar of aesthetic art but also as a repository of profound cultural heritage, delineating the distinctive folklore and cultural legacy of the Chaoshan region. However, with the acceleration of modernisation, traditional Guo molds production has been gradually replaced by mechanised production, the number of craftsmen has been drastically reduced, and the inheritance of skills is facing serious challenges. As a result, Chaoshan guo molds has gradually evolved into a precious collection of folk crafts. In the context of the contemporary information age, individuals tend to acquire information in a fragmented and visualised manner. This has led to an increased demand for the rapid consumption of information and an aesthetic experience. In light of this, it is crucial to investigate effective methods of visual information dissemination with a view to showcasing the distinctive appeal of traditional skills such as Chaoshan guo molds. From the perspective of semiotics theory, the article takes Chaoshan guo molds symbol culture in Chaoshan as an entry point, and begins by examining its development history, symbol characteristics, composition form, expression method, cultural connotation, and other relevant aspects. The article attempts to satisfy the public’s dual needs for cultural information and visual enjoyment by translating guo mold symbols into designs for tea ware products. It endeavors to bridge the gap between the abstract and the concrete, with the aim of enhancing the attraction and dissemination of traditional cultural information. This approach is intended to facilitate a deeper understanding of the cultural information in question. By translating the symbols of guo molds to meet the public’s dual needs for cultural information and visual enjoyment, we seek to establish a bridge between the abstract and the figurative, thereby enhancing the attractiveness and dissemination of traditional cultural information.